Process stability and microbial response of anaerobic membrane bioreactor treating high-strength kitchen waste slurry under different organic loading rates. (July 2017) - Xiao, Xiaolan; Shi, Wansheng; Huang, Zhenxing; Ruan, Wenquan; Miao, Hengfeng; Ren, Hongyan; Zhao, Mingxing
Abstract: Anaerobic membrane bioreactor (AnMBR) was applied for treating high-strength kitchen waste slurry obtained after the pretreatment of kitchen waste for oil recovery and solid separation. The process stability and microbial community structure of the AnMBR were investigated under different organic loading rates (OLRs). When the OLR increased from 4.7 kg-COD m −3 d −1 to 5.9 kg-COD m −3 d −1, 7.5 kg-COD m −3 d −1 and 9.3 kg-COD m −3 d −1, the digestion efficiency (i.e. conversion efficiency of COD to methane) increased from 68.8% to 78.1%, 81.5% and 84.4%, respectively, while the permeate COD all kept below 1500 mg L −1 . Additionally, the low VFA concentration (<300 mg L −1 ) and stable pH value around 7.5 under the four OLRs confirmed the robust stability of the AnMBR system. Furthermore, with the increase of OLR, the hydrolytic enzyme activity was enhanced, especially when the OLR increased from 4.7 kg-COD m −3 d −1 to 9.3 kg-COD m −3 d −1, the amylase, protease and lipase activities increased by 1.9-fold, 2.0-fold and 2.4-fold, respectively. Meanwhile, the increase of OLR had no obvious effects on the bacterial community but remarkable influence on the archaeal community as the dominant archaea shifted from Methanobacterium to Methanosaeta . Highlights: Stability of AnMBR treating high-strength kitchen waste slurry was evaluated. The AnMBR system exhibited a good flexibility to the OLR changes. The methane yield and organics digestion efficiency were enhanced as OLR increased. Activities of amylase, protease and lipase increased with elevation of OLR level. The archaeal community structure shifted in response to the OLR fluctuation.